Practice towards disposal of medicines (unused/expired drugs) among the patients visiting tertiary care teaching hospital in Haryana, India - Narwat, Arvind; Sindhu, Anjali (International Journal of Research in Medical Sciences, 2019)
Background: Awareness towards improper disposal of medicines and its hazardous impact on environment is one of the major issues which we are neglecting but needs to be focused. In general, expired medicines/waste medicines/ left out medicines are disposed in the garbage or, rinse in sink or flushed down toilet, which ends up in the water system and have a potential effect on ecosystem. With this background, the present study was conducted to assess the practice towards disposal of medicines (Unused/Expired Drugs) among the patients visiting tertiary care teaching hospital in Haryana. Methods: This study was a descriptive, cross-sectional study conducted through face-to-face interviews by using a validated structured Questionnaire in patients attending the OPD of PGIMS, Rohtak, Haryana. A total of 150 patients participated in this study. Results: Among the 150 Patients participated in the study, 94 were male and 56 were female. Most common class of medicines used were NSAIDS (34%). About the practice of disposal of medicines 62% of them threw into the dustbin (household garbage) 18% into the toilet/sink. About consequences of improper disposal (55%) of them answered that they were not aware. The most common reason for left out medicines in home was incompletion of the course due to getting relieved from disease (50%). Most common way of procuring medicine was purchased on prescription and surprisingly only 30% participants checked the expiry date of medicine before procuring. Among the participants 75% said that government should be responsible to create awareness for proper disposal of unused medicines. Conclusions: The present study brought out the current status and lacuna towards the disposal of medicines. Patients do not use all the medications and there is lack of knowledge about awareness of disposal of medicines and its consequences.